Synthesis of C8N9 Annulated Purines by Iron‐Catalyzed CH Amination. Issue 28 (3rd June 2013) - Maes, Jens; Rauws, Tom R. M.; Maes, Bert U. W.
Abstract : Purine and simple : A short synthesis for substituted annulated purine derivatives based on an Fe‐catalyzed direct amination reaction using oxygen as oxidant was developed (see scheme). Interestingly, iron proved to be superior to copper catalysis.